EFEKTIVITAS TUGAS ONLINE TERHADAP RESPONS BELAJAR SISWA SD KELAS V SELAMA PANDEMI COVID-19 - Ucu Lestari, Ainun; Rohani; Sukma Nugraha, Widdy (Bale Aksara, 2022)
The method used in this reswarch is quantitative descriptive method. The data collection techniques in this study used questionnaires or questionnaires. Based on the results of the study showed that: 1) the online assignment rate of classV SD in linkungan Kp.Legok Ringgit rw 09 moderate category with frequency (77.3%); (2) the learning response rate of elementary school V students in the Kp.Legok Ringgit rw 09 medium category environment with frequency (72.7%); (3) there is effectiveness of onine assignment to the learning response of elementary school students in the kp.legokringgit rw 09 environment of 11.56% while the remaining 88.44% effect rate is influenced by other variables that are not studied.